Building Students' Creative Thinking: Problem-Solving in Project-Based Culturally Responsive Teaching - Siti Inganah; Dwi Priyo Utomo; Baiduri Baiduri; Octavina Rizky Utami Putri; Retno Marsitin; Zulkifley Bin Mohamed (Didaktik Matematika, 2025)
Students' problem-solving skills remains a challenge because mathematics instruction often emphasizes procedures over creativity and rarely incorporates students' cultural contexts. This study explores the impact of Project-Based Culturally Responsive Teaching (CRT) on students' creative thinking and problem- solving skill, as well as teacher's perceptions of cultural integration in mathematics instruction. This explanatory sequential design study involved a class of 15 eighth- grade students and a mathematics teacher. Data were collected through observations, project assignments, tests, and questionnaires. The results showed that students' creative thinking indicatorsfluency, flexibility, and originalitywere in the excellent category, while elaboration increased from 79.17 (good) to 87.5 (excellent). Furthermore, there was a significant improvement in students' problem- solving skills, with an average pre-test score of 49.33 increasing to 64.33 (p < 0.05). The teacher responded that project-based CRT helped students develop more effective problem-solving strategies. These findings suggest that project-based CRT can foster students' creative thinking and problem-solving skill in mathematics. Teachers are encouraged to design problem-solving activities that connect mathematical concepts to students' cultural experiences to foster deeper understanding and more equitable learning opportunities